2021
DOI: 10.3389/fendo.2021.743962
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Genetic and Early-Life Environmental Factors in the Association Between Overweight or Obesity and Hypertension: A Population-Based Twin Study

Abstract: Aims/HypothesisWe aimed to explore whether and to what extent overweight or obesity could increase the risk of hypertension, and further to estimate the roles of genetic and early-life familial environmental factors in their association.MethodsThis prospective twin study was based on the Chinese National Twin Registry (CNTR), which collected information from self-report questionnaires. We conducted unmatched case-control analysis to examine the association between overweight or obesity and hypertension. And fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…A recent population-based study on 30,617 twin individuals showed that being overweight or obese was associated with a 94% increased risk of hypertension (OR = 1.94, 95% CI: 1.64~2.30). After controlling for all other variables, this association was mainly explained by genetics [ 38 ]. However, there is still no consensus on which specific genes have a direct role in both obesity and hypertension.…”
Section: Genetics Epigenetics and Mitochondrial Factors Related To Ob...mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent population-based study on 30,617 twin individuals showed that being overweight or obese was associated with a 94% increased risk of hypertension (OR = 1.94, 95% CI: 1.64~2.30). After controlling for all other variables, this association was mainly explained by genetics [ 38 ]. However, there is still no consensus on which specific genes have a direct role in both obesity and hypertension.…”
Section: Genetics Epigenetics and Mitochondrial Factors Related To Ob...mentioning
confidence: 99%
“…However, more recent studies have not been able to verify those results. A replication study by Goulet et al was done on a similar sample population and using similar methods as the study by Melka et al Their results showed that rs9930333 ( FTO ) was associated with increased body mass index, but not with increased systolic blood pressure [ 38 ]. A cross-sectional study also found no significant difference in genotypic frequencies of FTO rs9939609 SNP between hypertensive patients and healthy controls [ 42 ].…”
Section: Genetics Epigenetics and Mitochondrial Factors Related To Ob...mentioning
confidence: 99%
“…We estimated the linear effect between total GWG or trimester GWGRs and age-specific BAZ by using a generalized estimation equation (GEE) model and the non-linear effect by using a restricted cubic spline (RCS) linear regression model. The GEE model is a regression method that extends the generalized linear model to adjust for the correlation between a set of twins, which is commonly used in twin studies (28)(29)(30). The 5, 35, 65, and 95th percentiles of the distribution of specific trimester GWGRs were used in the RCS model.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review suggests that the application of information from obesity-related GWAS data can help shed light on the etiological mechanism of obesity-related metabolic risk [ 56 ]. Furthermore, a recent study carried out on twins showed that environmental factors such as smoking status, alcohol consumption and physical activity are key triggers in the development of obesity-associated hypertension [ 57 ], and a previous meta-analysis suggested that this association may be mediated by a SNP at the FTO locus [ 58 ]. Similarly, another GWAS also showed evidence linking alcohol intake with blood pressure through genes previously associated with alcohol intake, such as PINX1 , GATA4 , BLK , FTO and GABBR2 [ 50 ].…”
Section: Mets Traits Interacting With Environmental Factorsmentioning
confidence: 99%